Evaluating the Empowerment Potential of an International Sexual Support Website for Patients with Anorectal Malformations and Hirschsprung Disease, their Parents and Healthcare Providers - Spivack, Olivia K.C.; Schokker-van Linschoten, Irene K.; Spoel, Marjolein; Lemli, Annette; Aminoff, Dalia; Pakarinen, Mikko; de Blaauw, Ivo; Ijsselstijn, Hanneke; Petit-Steeghs, Violet (European Journal of Pediatric Surgery, 2025)
Research indicates that the sexual support needs of patients with anorectal malformations (ARM) and Hirschsprung disease (HD) are often not addressed by patients, parents, and healthcare professionals (HPs) in their interactions. An international support website was developed to empower stakeholders, by addressing identified barriers. This study aimed to explore the empowerment potential of this disease-specific tool.Two online surveys were disseminated between May 1 and October 1, 2023; one for HPs and another for patients/parents. The surveys sought to assess and understand the website's expected empowerment effect. Empowerment was conceptualized using patient/professional empowerment models. Data were descriptively analyzed.A total of 12 patients (ARM, n = 11; HD, n = 1), 17 parents (ARM, n = 9; HD, n = 8), and 20 HPs responded to the survey. HPs largely expected the website to have a positive empowerment effect, by providing a sense of meaning, information, support, and opportunities to learn and grow. Less of an effect was expected for “freeing up resources.” For patients and parents, an empowerment effect was also expected, by generating the knowledge, skills, attitudes, and self-awareness necessary to influence their own behavior and by providing a sense of meaning and coherence. Respondents experienced the website positively, yet one patient and one parent considered the website “fully complete.” Inclusivity, cultural sensitivity, and accessibility were highlighted as focus points.To increase the website's empowerment potential, attention should be paid to inclusivity, cultural sensitivity, and accessibility, as well as its implementation within the (institutional) contexts where patients, parents, and HPs interact.
Keywords: ERNICA; ERN eUROGEN; European Reference Network; rare disease; digital health